Dalam Pusaran Deepfake Pornografi: Menakar Pertanggungjawaban Pidana Platform Digital - Huda Alghiffary, Habil; Rapik, Mohamad; Wahyudhi, Dheny (Faculty of Law, Universitas Jambi, 2026)
The development of artificial intelligence technology has given rise to the phenomenon of pornographic deepfakes, which allow the manipulation of a person's face or identity into sexual content without consent. The distribution of this content is generally facilitated by digital platforms with a wide distribution reach. The problem arises because Indonesian positive law does not explicitly regulate pornographic deepfakes or the limits of criminal liability for digital platforms. This study aims to analyze Indonesian criminal law regulations related to the position of digital platforms as legal subjects and to formulate the limits of criminal liability for the distribution of pornographic deepfake content. As a normative juridical approach, this study uses a legislative and conceptual approach, through an examination of the Electronic Information and Transactions Law, the Pornografi Law, the 2023 Criminal Code, and Regulation of the Minister of Communication and Informatics Number 5 of 2020. The results show that the regulations are still partial and do not explicitly regulate the responsibility of digital platforms. Platforms cannot be automatically criminalized, but can be held accountable if proven to have an active role, negligence, or systemic negligence. This study concludes the need for more adaptive and balanced criminal law policy updates to provide legal certainty and effective protection for victims. ABSTRAK Perkembangan teknologi kecerdasan buatan telah melahirkan fenomena deepfake pornografi yang memungkinkan manipulasi wajah atau identitas seseorang ke dalam konten seksual tanpa persetujuan. Penyebaran konten tersebut umumnya difasilitasi oleh platform digital yang memiliki jangkauan distribusi luas. Permasalahan muncul karena hukum positif Indonesia belum secara eksplisit mengatur deepfake pornografi maupun batas pertanggungjawaban pidana platform digital. Penelitian ini bertujuan untuk menganalisis pengaturan hukum pidana Indonesia terkait posisi platform digital sebagai subjek hukum serta merumuskan batas pertanggungjawaban pidana dalam penyebaran konten deepfake pornografi. Sebagai yuridis normative, penelitian ini dengan pendekatan perundang-undangan dan konseptual, melalui kajian terhadap Undang-Undang Informasi dan Transaksi Elektronik, Undang-Undang Pornografi, Kitab Undang-Undang Hukum Pidana Tahun 2023, serta Peraturan Menteri Komunikasi dan Informatika Nomor 5 Tahun 2020. Hasil penelitian menunjukkan bahwa pengaturan masih bersifat parsial dan belum secara tegas mengatur tanggung jawab platform digital. Platform tidak dapat dipidana secara otomatis, namun dapat dimintai pertanggungjawaban apabila terbukti terdapat peran aktif, pembiaran, atau kelalaian sistemik. Penelitian ini menyimpulkan perlunya pembaruan kebijakan hukum pidana yang lebih adaptif dan berimbang guna memberikan kepastian hukum serta perlindungan efektif bagi korban.